Meningkatkan Keterampilan dan Kreativitas Siswa Menggunakan Implementasi Teori Domino di SMAN 1 Batukliang Utara - Ayes Malona Siboro; Fathul Maulina Wahidah; Lalu Riski Wirendra Putra; Sahin Two Lestari; Syaftirridho Putri; Rendi Bahtiar Pratama; I Gede Adhitya Wisnu Wardhana (Lembaga Pengembangan Kinerja Dosen, 2024)
In this era of globalization, having critical and creative thinking skills is a capability that students must possess to compete and face the future. Community service conducted at SMAN 1 Batukliang Utara aimed at developing students’ skills and creativity was carried out by adopting the domino theory approach. The results of the pre-test showed that the average student score after statistical testing was 64.06. However, after participating in the community service activities and taking the post-test, the average score increased to 89.81, indicating an improvement in students’ understanding by 40.20%.